A checklist of Eucnemidae (Coleoptera: Elateroidea) from Iran - Kovalev, Alexey V.; Ghahari, Hassan (Zootaxa, 2024)
The distribution of Eucnemidae (Coleoptera: Elateroidea) of Iran is summarized and an annotated checklist of the Iranian Eucnemidae is provided. A total of 16 species within 13 genera in four subfamilies of the family are listed.